A Critical Look at the Efficient Market Empirical Research Literature As It Relates to Accounting Information. - Downes, David; Dyckman, Thomas R. (The Accounting Review, 1973)
The article discusses efficient market empirical research literature in relation to accounting information. The studies discussed in the article questioned the frictionless nature of the hypothesis as usually expressed. The authors believe that efficient-markets research in relation to financial accounting is the most important thrust made by accounting researchers in the past decade. By its very nature, empirical research is time consuming and messy. Furthermore, conclusions are always subject to reservations.